The use of the Management Plan by Protected Area Managers (Research, Society and Development, 2023)
During the research there was a need for information on the progress of the activities planned in the Management Plan, and this information was collected through forms and filled in by the managers of the CUs. The specific objectives of this work are: to analyze the use of the management plan by the managers of the protected areas and to evaluate the fulfillment of the planning of the management programs contained in the management plan of the protected areas studied. The analysis of this information was performed by adapting the Tracking Tool. It was identified in the studied areas, the Madeira River Sustainable Development Reserve (RDS do Rio Madeira) and the Caverna Maroaga Environmental Protection Area (APA Maroaga), that there is an effective use of management plans, by the managers of these protected areas, as well as how the strategically planned management programs are carried out during the preparation of the Plans. The use of the Management Plan as an administrative instrument for the management of the studied CUs is related to and directly influences the empowerment of the actors that make up the management council and constitutes an important governance instrument. It is concluded that the adoption of management practices during the Plan's implementation helps to consolidate the strategic planning initiated during the Plan's preparation phase. The use of medium-term tactical planning contributes to the management council members acting efficiently and directly in the management of the protected area.